Pro OpenGL Es for iOS - Smithwick, R. Michael (Apress, 2011)
In Pro OpenGL ES for iOS, you'll find out how to harness the fullÆpower of OpenGL ES, and design yourŏwn 3D applications by building a fully-functional 3D solar system model using Open GL ES! OpenGL has set the standard for 3D computer graphics, and is an essential aspect of iPhone, iPad, and iOS development. This bookŏffers everything you need to know, from basic mathematical conceptsÆtoădvanced coding techniques. You'll learn by building this fascinating 3D solar system simulator! After introducing OpenGL ES, Pro OpenGL ES for iOS explains the basics of 3D math and thenŏrients you to the iOS-native 3D libraries you'll be using inÆyour own 3D games and the solar system project you'll buildŭsing this book.ÆThrough the solar system example project, you'll learn how to incorporate a variety of graphic and animation techniques into your applications. You will also discover howÆthe full spectrum of 3D development that awaits, with topics such as lighting, texture-mapping, modeling, shaders, blending modes, andÆseveral moreădvanced concepts. By the time you finishÆPro OpenGL ES for iOS, you'llÆhave learned allÆthe skills you'll need to build your own incredible 3Dăpplications, based on one of the most powerful 3DÆlibraries available.